2011
DOI: 10.1089/end.2010.0638
|View full text |Cite
|
Sign up to set email alerts
|

Renal Parenchymal Damage After Percutaneous Nephrolithotomy with One-Stage Tract Dilation Technique: A Randomized Clinical Trial

Abstract: Although the one-stage tract dilation technique reduced radiation exposure and access time, in the short term, it may cause more parenchymal damage than the gradual dilation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
1
31
0
2
Order By: Relevance
“…Aminsharifi, et al 13 condujeron un estudio que reveló el daño causado al parénquima renal comparando la dilatación en un paso contra la dilatación secuencial a través de la captación de tecnecio 99 en una gammagrafía con ácido dimercaptosuccínico (DMSA), encontrando que 14 de 29 pacientes con la técnica en un paso presentaron una nueva cicatriz en el parénquima, en comparación con 2 de 29 pacientes del grupo de dilatación secuencial. En nuestro estudio se pretendió medir de manera indirecta la función renal con los valores séricos de creatinina; sin embargo, tanto la captación de tecnecio 99 en la gammagrafía con DMSA como los valores séricos de creatinina no son la modalidad diagnóstica de elección para determinar la función renal.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aminsharifi, et al 13 condujeron un estudio que reveló el daño causado al parénquima renal comparando la dilatación en un paso contra la dilatación secuencial a través de la captación de tecnecio 99 en una gammagrafía con ácido dimercaptosuccínico (DMSA), encontrando que 14 de 29 pacientes con la técnica en un paso presentaron una nueva cicatriz en el parénquima, en comparación con 2 de 29 pacientes del grupo de dilatación secuencial. En nuestro estudio se pretendió medir de manera indirecta la función renal con los valores séricos de creatinina; sin embargo, tanto la captación de tecnecio 99 en la gammagrafía con DMSA como los valores séricos de creatinina no son la modalidad diagnóstica de elección para determinar la función renal.…”
Section: Discussionunclassified
“…Cuando se identifica alguno de estos factores de riesgo se recomienda realizar el trayecto de nefrostomía con la técnica convencional 11 . Con el fin de reducir estas complicaciones, la fuerza radial aplicada es crucial, utilizando movimientos rotacionales durante el proceso gradual para reducir así el desplazamiento de la unidad renal y la tasa de falla a un 7% en pacientes con cirugía previa 8,13,14 . Dentro de las limitaciones al realizar este estudio encontramos las dificultades para la evaluación de la función renal de manera directa.…”
Section: Discussionunclassified
“…However, it was demonstrated that although the one stage tract dilation technique reduced radiation exposure and access time in the short term, it may cause more parenchymal damage than the gradual dilation technique. 13 They described a dilator composed of an 8F polyurethane tube cemented to a gradually tapering polyurethane dilator of the desired size (10F to 34F) that was passed over a guidewire into the pyelocaliceal system, with the 8F portion entering the proximal part of the ureter. 11 Whilst other described a single dilation with a 25 F or 30 F Amplatz dilator advanced over an Alken guide or an 8 F dilator.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different treatment modalities might be considered for large upper- and mid-ureteral stones. PNL was recommended for large upper-ureter stones in the guideline [2;] however, scar formation or progression rates have been reported as 11 to 48.3% [8]. For this reason, PNL for pure proximal ureteral stones more than 15 mm is not preferred in our institution.…”
Section: Discussionmentioning
confidence: 99%